2021
DOI: 10.1007/s10140-021-01907-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on CT scans ordered from the emergency department for abdominal complaints

Abstract: Purpose The COVID-19 pandemic has affected healthcare systems and patients alike across the USA. We seek to elucidate changes in abdominal imaging ordered from the emergency department (ED) in a healthcare system undergoing non-surge conditions in April 2020 compared to April 2019. Methods We performed a retrospective, observational study comparing patients undergoing CT scans of the abdomen and pelvis ordered from the ED in April 2020 vs. April 2019 at a single healthcare center. Via review of the radiology r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…However, they found that the number of scans conducted quickly rebounded back to the historical amount in the months of June and July [ 22 ]. This has been a consistent finding in multiple other studies [ 18 , 19 , 33 35 ], which have echoed substantial decreases in the amount of CT scans ordered early in the pandemic.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, they found that the number of scans conducted quickly rebounded back to the historical amount in the months of June and July [ 22 ]. This has been a consistent finding in multiple other studies [ 18 , 19 , 33 35 ], which have echoed substantial decreases in the amount of CT scans ordered early in the pandemic.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, examining CT scans of the abdomen and pelvis for all abdominal complaints from two hospitals in Utah, Griffith et al (2021) reported a 31.6% decrease in CT abdomen and pelvis scans in April 2020 compared to April 2019, while having a higher positivity rate in 2020. However, the only abdominal complaints that were significantly different in 2020 for positivity rate were appendicitis, cholangitis, and colitis, whereas the other 14 abdominal complaints showed no difference between the two timepoints [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease is less than the change in volume of ED ultrasounds performed by the radiology department, which neared a 60% decline. The relative decrease in utilization of radiology department ultrasound during the pandemic was certainly accentuated by the change in distribution of clinical presentations to the ED [28] and in practitioner decisions to defer imaging of lower acuity patients [14,29]. Another factor leading to our decreased ED imaging utilization in 2020 can be understood by the study population we serve.…”
Section: Discussionmentioning
confidence: 99%
“…However, the converse has also been reported where no differences in complications or severity in AA presentation were seen in other regions. In a retrospective study by Griffith et al [ 132 ] comparing 2020 and 2019 AA admissions, there was an increased admission rate (40.8% vs 34.1%, P = 0.036)[ 132 ]. Kohler et al [ 133 ] revealed in a population-based study in Germany that there was no difference in the number of perforated AA diagnosed during the pandemic or pre-pandemic[ 133 ].…”
Section: Aa and The Covid-19 Pandemicmentioning
confidence: 99%